Sistema de detección de obstáculos para invidentes - Alvarado, Juan David; Mosquera, Víctor Hugo (Visión electrónica, 2016)
Nowadays, mobility for the blind has a high degree of difficulty due to environmental conditions, therefore, assistive devices have been developed in order to improve their quality of life, obstacle detection system for blind people aims to detect obstacles by the use of ultrasonic sensors, the data received by the sensors are transmitted to the blind person through a sound module indicating the presence of an object, sensors are incorporated into a vest of easy use that contributes user´s safety when walking. In the development of this article are shown both implementation and operation of the system, showing the obstacle detection.